ANALISIS PENGARUH INFORMASI PROFITABILITAS YANG DIUKUR DENGAN PENDEKATAN LABA PER LEMBAR SAHAM(EARNING PER SHARE /EPS) DAN NILAI TAMBAH EKONOMI (ECONOMIC VALUE ADDED /EVA) TERHADAP CAPITAL GAIN (Penelitian Pada Perusahaan Perbankan Yang Terdafar Di Bursa - Lilis Puspitawati; Nurdiansyah - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
This research analyzed Earning per Share (EPS) and Economic Value Added (EVA)influence the banking company's stock price changes in Indonesia Stock Exchange. The sampleused is banking company which actively in Indonesia Stock Exchange trading of year 2000-2009, isalways publishing financial reports every year and the company included the biggest bankingcompany by assets.This research is using descriptive analysis method with quantitative approach. Sample ofdata is reports balance sheet, profit / loss and share price of banking statistics for 2006 to 2009. Thisresearch using the dependent variable stock price changes, while the independent variable isearningpershare (EPS) and economic value added (EVA).Based on the research that earnings per share and economic value added simultaneouslydoes not significantly influence change of stocks price on five banking companies which are listed inIndonesia Stock Exchange. Based on the partial testing earnings per share did not have significantinfluence on change of stock price in the banking companies. And partial test of the influence ofvariable economic value added can concluded that economic value added has no significant effecton stock price movements on five banking companies listed in Indonesia Stock Exchange